Comparison of clinical efficacy of diode laser and erbium, chromium: Yttrium, scandium, gallium, and garnet for implant stage 2 recovery procedure - A randomized control clinical study - Sahana Selvaganesh; Priya Lochana Gajendran; Thiyaneswaran Nesappan; Abhinav Rajendra Prabhu (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim is to compare the clinical efficacy of diode laser and erbium, chromium-doped yttrium, scandium, gallium, and garnet (Er, Cr:YSGG) laser for implant stage 2 recovery procedure. Materials and Methods: A total of 30 patients who had undergone dental implant placement were included in this study. The subjects were randomly allocated into three groups. Group 1 patients (n = 10) had implant recovery using diode laser, Group 2 (n = 10) implant recovery with Er, Cr:YSGG and conventional scalpel method (n = 10) was the third group. The pain assessment was recorded using visual analog scale (VAS scale), time taken for the procedure, intra-operative bleeding, time taken for healing were recorded for the three groups. Results: Data were tabulated and the results were analyzed using SPSS software version 26. Mann-Whitney U-test was used to compare the postoperative analgesic used, postoperative VAS score, the time taken for recovery and time taken for healing between the three study groups. Results were considered to be statistically significant when P < 0.05.Operation duration under Er, Cr:YSGG were much faster than the diode laser, however the results were not statistically significant (P = 0.051). The operation time under Er, Ch: YSGG and laser were faster than the conventional scalpel group (P = 0.000). The time taken for healing was faster in the Er, Cr:YSGG laser group than the diode laser and the scalpel group (P = 0.000). VAS scale at day 0 was higher in the conventional group than the two laser groups (P = 0.000). Conclusion: Considering the advantages of both these laser systems such as less anesthesia, less surgical trauma and faster healing, and post-operative comfort, lasers are an effective tool for implant stage two recovery techniques. However, since diode lasers are more cost effective when compared to Er, Cr:YSGG, diode lasers may meet the clinical needs when compared to hard-tissue lasers.